Women in Feminism and Politics - Mohammad Shabbir (International Institute of Islamic Thought, 1998)
The debate about Islamization of the human sciences, of physical sciences, of linguistics and aesthetics has become global. If Islamization is vital and a necessity for the rejuvenation of the new Islamic civilization, women and families cannot escape from Islamization. Zeenath Kausar has argued the same in her book. Her arguments for the necessity of IslamizaLion of women's and family's problems are pioneering ideas on the subject. The book comprises four chapters and each chapter follows the general framework of the methodology of Islamization of Knowledge: presentation of the Western theories followed by their critical analysis and Islamic alternatives. The firsl chapter titled "Women in Western Political Theory: An Islamic Analysis," surveys Western political thinkers from classical to postmodern (Plato to Foucault), on their views on women. Discussing the arguments of these thinkers, especially from Plato to Hegel on the ineligibility of women for political participation, she contends that Western political thought is essentially misogynistic. Plato argues that women, children, and slaves mainly belong to the appetitive class when compared to the classes of "philosophers" and "soldiers," where men predominate. Aristotle denies women citizenship; he contends that women are nol capable of political participation. St. Augustine and St. Thomas Aquinas, relying on biblical sources dealing with the creation and the ...